Dampak dari Pembangunan Jalan Lintas Selatan (JLS) terhadap Kawasan Pesisir Pantai di Kabupaten Malang Selatan - Herman Cahyo Diartho Cahyo (Ecoplan, 2020)
Abstract - Regional disparities occur because each region has different endowment factors. These factors take human resources, geographic area, development facilities, and infrastructure availability. This is reinforced by the opinion of economists from the neoclassical school, including Walter Isard (1950,63), Myrdal (1976, 56-59 and 62-65), Friedmann (1979, 221), and finally Douglass (1979, 76). The research results explain that the road infrastructure of Lintas Selatan Road in the South Malang Regency area provides positive externalities to the local economic development of coastal communities. It also increases capitalization in the coastal fisheries industry's input sector by increasing investment and increasing the number of vessels. Negative externalities occur fast and massive pull of natural resources in the coastal areas to all economic centers in Malang Raya. The availability of coastal natural resources is still in the sustainable category, although exploration has increased after constructing the South Cross Road (JLS) infrastructure. The analytical tool method used is Maximum Sustainable Yield / MSY and Economic Valuation (Contingent Valuation Method / CVM) to examine the results of the formulation of the Willingness to Pay / WTP value and the value of Willingness to Act / WTA. The attraction of the coastal area resources is described qualitatively. The Sustainable Development Paradigm is used in explaining the externalities of the Southern Cross Road (JLS) infrastructure to the development of coastal areas in the South Malang Regency. Keywords: Coastal Areas, Natural Resources and Sustainable Development